A Mediterranean Lifestyle Is Associated With Lower Hypertension Prevalence and Better Aerobic Capacity Among New England Firefighter Recruits. Issue 7 (July 2020) - Lan, Fan-Yun; Fernandez-Montero, Alejandro; Yiannakou, Ioanna; Marinos-Iatrides, Orestes; Ankeny, Jacob T.; Kiser, Jeffrey; Christophi, Costas A.; Christiani, David C.; Sotos-Prieto, Mercedes; Kales, Stefanos N.
Abstract : Objective: Examine the association between healthy Mediterranean lifestyle practices and cardiovascular disease (CVD) risk factors among New England firefighter recruits. Methods: A MEDI-Lifestyle score was used to measure adherence to a Mediterranean lifestyle (not smoking, increased physical activity, high adherence to Mediterranean diet, non-obese body mass index, decreased screen time, adequate nightly sleep, and napping) among the recruits. MEDI-Lifestyle scores were cross-sectionally analyzed with blood pressure, aerobic capacity, and other CVD risk factors. Results: Among 92 recruits, high adherence to MEDI-Lifestyle was significantly associated with a decreased risk of prevalent hypertension (odds ratio [OR] = 0.14 [0.03–0.71]) and a greater probability of high aerobic capacity (OR = 5.80 [1.05–32.05]) as compared with low adherence in age- and sex-adjusted analyses. Conclusions: Increased adherence to MEDI-Lifestyle is associated with a better CVD risk profile in firefighter recruits.